2011
DOI: 10.1111/j.1939-1668.2011.01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Valuing the Intuitive: Reintroducing Design into Interior Design Education

Abstract: Recently I observed a facilitated session with 15 invited participants representing interior design, structural engineering, architecture, industrial and product design, graphic design, lighting design, landscape architecture, design research, technology, construction management, and manufacturing who discussed the driving factors perceived as influencing collaboration across design-related professions. Although the discussion centered on collaboration, I noticed an interesting subtext emerging throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The study found that from the user-centred point of view, using the probing method helped to conceptualize the variant qualities connected to the space as well as promoted to create a dialogue between various user groups as well as between designers and non-designers. The method also focuses on the feelings and emotions in learning process that need to be taken more seriously in current interior design education (Budd 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The study found that from the user-centred point of view, using the probing method helped to conceptualize the variant qualities connected to the space as well as promoted to create a dialogue between various user groups as well as between designers and non-designers. The method also focuses on the feelings and emotions in learning process that need to be taken more seriously in current interior design education (Budd 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Number 4 2017 In the ID context, EI has been identified as important in relation to design intuition (Budd, 2011), leadership, compassionate design, and constructing design narratives (Danko, 2003), but the quantitative aspect of interior designers' and students' EI has not been broached.…”
Section: Divergent Methods To Conceptualize Eimentioning
confidence: 99%
“…Crucial to the inquiry in environmental design is the phenomenological translation of the essence of one’s action and perception into architectonic dimensions, not only the examination of the impact of material elements on aesthetic or practical use. Due to the multidimensional, multimodal, and multisensory nature of spatial perception, no single methodology or prescriptive measure can sufficiently explain human responses to the spatial attributes and sensory stimuli ( Budd, 2011 ). Regardless of some controversy, the reciprocal contribution of phenomenology and psychology to each other has been acknowledged for many years, and the contribution of phenomenology to environmental psychology and design has been noted as it provides insight into what one’s experience and perception are like for the subject from its first-person point of view ( Seamon, 1982 ).…”
Section: Introductionmentioning
confidence: 99%